Живописные реминисценции в фильме Владимира Мотыля «Белое солнце пустыни» - ДИМЕШИ, ЖУЖАННА (SlavVaria, 2021)
References to Fine Arts in Vladimir Motil’s Feature Film “White Sun of the Desert”. The Soviet feature film “White Sun of the Desert” (1970) by Vladimir Motil is considered a landmark in many ways. The circumstances of filming, screening, release, audience reaction, and the genre and formal language of the film itself all are significant. The article focuses on the filming process in the experimental studio ETO, the specificities of the genre called eastern and some features of the movie’s formal language, namely, the reminiscences of paintings by artists such as Korovin, Kuznetsov, Kustodiev, Larionov, Malevich, Sarian, Jakulov from the beginning of the 20th century.